2020
DOI: 10.1111/jbi.14009
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific differentiation: Implications for niche and distribution modelling

Abstract: Aim Mounting evidence suggests that failure of species distribution models to integrate local adaptation hinders our ability to predict distribution ranges, raising the question of whether modelling should be performed at the level of species (clade models) or intraspecific lineages (subclade models), characterized by the restricted availability of occurrence points. While Ensembles of Small Models (ESMs) offer an attractive framework for small datasets, their evaluation remains critical. We address these issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 93 publications
5
55
0
Order By: Relevance
“…The performance (or accuracy) of ENMs has previously been found to be influenced by the number of occurrence records, especially small sample sizes (Collart et al., 2021; van Proosdij et al., 2016). Given this concern would also exist with our ensemble ENMs of focal species within the EAS–ENA disjunct plants, we used a sample size of > 20 occurrence records.…”
Section: Discussionmentioning
confidence: 99%
“…The performance (or accuracy) of ENMs has previously been found to be influenced by the number of occurrence records, especially small sample sizes (Collart et al., 2021; van Proosdij et al., 2016). Given this concern would also exist with our ensemble ENMs of focal species within the EAS–ENA disjunct plants, we used a sample size of > 20 occurrence records.…”
Section: Discussionmentioning
confidence: 99%
“…How different plant species can adapt to a changing climate represents a crucial ecological and evolutionary question. As widely distributed species often possess many genetic lineages or subspecies (Van Rossum et al., 2018 ), revealing their population structure may help to predict their response to different environmental conditions at present and under future conditions (Collart et al., 2021 ). In many European plant species, a phylogeographic pattern can be found that resulted from the survival in different refugia during the last glacial maximum (LGM) (Bagnoli et al., 2016 ; Beatty & Provan, 2011 ; Krebs et al., 2019 ; Listl et al., 2017 ; Roces‐Díaz et al., 2018 ; Schwarzer & Joshi, 2019 ; Sebasky et al., 2016 ; Taberlet et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…If we are interested in how species can adapt to these habitat changes, their genetic background has to be considered (Anderson et al., 2011 ; Bowles & Whelan, 1996 ; Corlett, 2017 ; McMahon et al., 2014 ; Vandergast et al., 2008 ). The inclusion of intraspecifc lineages is of strong importance here as it has been proven to substantially impact analyses on ecological niche modeling (Collart et al., 2021 ). Therefore, we included the phylogenetic data to investigate possible response differences in S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we have tried to overcome the limitations of any one approach by combining multiple methods and constructing ensemble species distribution models with multiple algorithms, and their results are largely congruent. Recent studies have also recommended null models as a means of exploring the robustness of species distribution models (Collart et al, 2021); for example, a null model could conceivably test if range-restricted conifer taxa (located anywhere on the globe) always lead to high percent relative contributions of palaeoclimates in species distribution models. However, range-restricted conifer taxa can show low contributions from palaeoclimate variables to their current distributions and widespread taxa can show high contributions, as seen in species distributions models from the LGM (Figure S1).…”
Section: Discussionmentioning
confidence: 99%